PENGARUH AUDITOR SWITCHING, PROFITABILITAS, UKURAN PERUSAHAAN, DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG: THE EFFECT OF AUDITOR SWITCHING, PROFITABILITY, COMPANY SIZE, AND AUDIT OPINION ON AUDIT REPORT LAG - Rezi, Rezi; Indrawati, Novita; Azhar L, Al (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study aims to examine and analyze the effect of auditor switching, profitability, firm size, and audit opinion on audit report lag. The population of this study is the property & real estate sector companies listed on the Indonesia Stock Exchange in 2016-2019. The sampling method used purposive sampling method, the research sample obtained was 31 data with 4 years of observation. The tool used to analyze is multiple linear regression analysis and hypothesis testing with t test. The results of this study indicate that the results of this study found that auditor switching, profitability, firm size, and audit opinion have an effect on audit report lag.